Tree Shrew Is a Suitable Animal Model for the Study of Epstein Barr Virus - Xia, Wei; Chen, Honglin; Feng, Yiwei; Shi, Nan; Huang, Zongjian; Feng, Qingyuan; Jiang, Xu; He, Guangyao; Xie, Mao; Lai, Yongjin; Wang, Zhi; Yi, Xiang; et al. (Frontiers in Immunology, 2022)
Epstein-Barr virus (EBV) is a human herpesvirus that latently infects approximately 95% of adults and is associated with a spectrum of human diseases including Infectious Mononucleosis and a variety of malignancies. However, understanding the pathogenesis, vaccines and antiviral drugs for EBV-associated disease has been hampered by the lack of suitable animal models. Tree shrew is a novel laboratory animal with a close phylogenetic relationship to primates, which is a critical advantage for many animal models for human disease, especially viral infections. Herein, we first identified the key residues in the CR2 receptor that bind the gp350 protein and facilitate viral entry. We found that tree shrew shares 100% sequence identity with humans in these residues, which is much higher than rabbits (50%) and rats (25%). In vitro analysis showed that B lymphocytes of tree shrews are susceptible to EBV infection and replication, as well as EBV-enhanced cell proliferation. Moreover, results of in vivo experiments show that EBV infection in tree shrews resembles EBV infection in humans. The infected animals exhibited transient fever and loss of weight accompanied by neutropenia and high viremia levels during the acute phase of the viral infection. Thereafter, tree shrews acted as asymptomatic carriers of the virus in most cases that multiple EBV-related proteins could be detected in blood and tissues. However, a resurgence of EBV infection occurred at 49 dpi. Nanopore transcriptomic sequencing of peripheral blood in EBV-infected animals revealed the dynamic changes in biological processes occurring during EBV primary infection. Importantly, we find that neutrophil function was impaired in tree shrew model as well as human Infectious Mononucleosis datasets (GSE85599 and GSE45918). In addition, retrospective case reviews suggested that neutropenia and neutrophil dysfunction may play an important role in EBV escaping host innate immune response, leading to long-term latent infection. Our findings demonstrated that tree shrew is a suitable animal model to evaluate the mechanisms of EBV infection, and for developing vaccines and therapeutic drugs against EBV.